"Gotta Make Your Own Heaven": Guns, Safety, and the Edge of Adulthood in New York City, 2018-2019 - Swaner, Rachel ([Verlag nicht ermittelbar], 2021)
This project investigated the experiences of New York City youth ages 16-24 who were at high risk for gun violence (e.g., carried a gun, been shot or shot at). Youth participants were recruited from three neighborhoods with historically high rates of gun violence when compared to the city as a whole--Brownsville (Brooklyn), Morrisania (Bronx), and East Harlem (Manhattan). This study explores the complex confluence of individual, situational, and environmental factors that influence youth gun acquisition and use. This study is part of a broader effort to build an evidence-based foundation for individual and community interventions, and policies that will more effectively support these young people and prevent youth gun violence. Through interviews with 330 youth, this study seeks to answer these questions: What are the reasons young people carry guns? How do young people talk about having and using guns? What are young people's social networks like, and what roles do guns play in thesenetworks? Interviews covered the following topics: neighborhood perceptions; perceptions of and experiences with the police, gangs, guns, and violence; substance use; criminal history; and demographics: race, gender, age, legal status, relationship status, living situation, location, number of children, drug use, and education.